Improving Teachers' Ability to Apply Learning Models Through Classroom Supervision Activities by the Principal of SD Negeri Tritih Kulon 09 in Semester I of the 2018/2019 Academic Year - Ikah Ikah; Johariyah Johariyah (Proceedings Series on Social Sciences & Humanities, 2023)
In carrying out the learning process at school, a teacher should be able to choose and utilise learning models that are in accordance with the learning material. In general, teachers rarely use learning models in every learning process, due to the lack of teacher understanding of learning models that can facilitate teachers in implementing the learning process in the classroom. Actually, there are many learning models that can be used by every teacher in the learning process. By using appropriate learning models, of course, students will be motivated to learn, and this will have a positive impact on their learning outcomes.The main problem in the study, namely "Can the application of learning models through classroom supervision activities improve the quality of learning in students at SD Negeri Tritih Kulon 09?". Based on the results of this study, it is concluded that the application of learning models through classroom supervision by school principals has proven successful in improving the ability of SD Negeri Tritih Kulon 09 teachers in managing the learning process. In addition, by increasing the ability of SD Negeri Tritih Kulon 09 teachers in managing the learning process, not only the students' learning process is more meaningful but also their learning outcomes increase.